Diagnosis dan Penatalaksanaan Tumor Ganas Laring - Dolly Irfandy; Sukri Rahman; Dolly Irfandy (Fakultas Kedokteran, Universitas Andalas, 2015)
Abstrak Laring berperan dalam koordinasi fungsi saluran aerodigestif atas seperti bernafas, berbicara dan menelan.Laring terbagi tiga yaitu supraglotis, glotis dan subglotis. Laring merupakan daerah tersering kedua untuk kasuskarsinoma sel skuamosa kepala-leher, biasanya berhubungan dengan tembakau dan alkohol. Lebih dari 95% kasustumor ganas laring adalah karsinoma sel skuamosa. Pasien tumor ganas laring datang dengan berbagai keluhanseperti disfonia, obstruksi jalan napas, disfagia, odinofagi dan hemoptisis. Diagnosis tumor ganas laring ditegakkanberdasarkan anamnesis, pemeriksaan klinis menggunakan endoskopi kaku, serat optik dan biopsi. Penatalaksanaantumor ganas laring tergantung stadium dengan modalitas berupa operasi, kemoterapi, radiasi atau terapi kombinasi.Dilaporkan kasus laki-laki 53 tahun dengan karsinoma glotis stadium III (T3N0M0) squamous cell ca keratinized welldifferentiated. Penatalaksanaan pada pasien ini dengan melakukan laringektomi total.Kata kunci: Tumor ganas laring, karsinoma, laringektomi, tembakau Abstract Larynx plays a certain role in coordinating functions of the upper aerodigestive tract, such as respiration,speech, and swallowing. The larynx is divided into three region; supraglottic, glottic, and subglottic. Larynx is thesecond most common site for squamous cell carcinoma in the head and neck and usually related to tobacco andalcohol exposure. Primary malignant tumors of the larynx are squamous cell carcinomas can found more than 95% ofcases. Patients with laryngeal tumors usually present with complaints of hoarseness, respiratory obstruction,dysphagia, odynophagia and hemoptysis. Diagnosis of laryngeal cancer is made by medical history, clinicalexamination using a rigid or fiberoptic endoscope and biopsy. Management of laryngeal tumour depends on stadiumwith various modality included surgery, chemotheraphy, radiotheraphy or combined therapy. Reported case of 53years old male with Glottic carcinoma of the larynx stage III (T3N0M0) squamous cell ca keratinized well differentiatedis presented. The treatment undergoes with total laryngectomy.Keywords: Laryngeal cancer, carcinoma, laryngectomy, tobacco